THE FOREIGN EXPERIENCE IN THE CONSTRUCTION OF TUNNELS IN SEISMIC ZONES - Kaufman, L. L.; Lysikov, B. O.; Labinskyi, K. M.; Komyshan, I. O. (Science and Transport Progress, 2008)
The review of foreign experience of the tunnel construction in earthquake regions is shown in this paper. The technical solutions for prevention of the earthquake consequences and the examples of building and reconstruction of the tunnels in earthquake regions are listed below.